English-Inuit hostilities at Cape Charles (Labrador) in 1767 - Rollmann, Hans (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2015)
In 1767, three English fishers associated with Nicholas Darby’s fishing and trading enterprise in southern Labrador were killed by Inuit. In response to this violence, a contingent of British soldiers from newly established York Fort pursued the alleged perpetrators, killed several, and captured others. Among the captives was an Inuk woman named Mikak as well as the future first Moravian Inuk convert, the youth Karpik. The hostilities of 1767 cannot be fully explored merely by following the narrative of colonial authorities and traders. If the Moravian records are consulted, the notorious murder near Cape Charles in 1767 appears to have had a more complex causation than has hitherto been suggested, one that may include some European culpability in these events. Instead of the unprovoked murder of three Europeans by Inuit during a robbery, it may have been a violent act of self-defence to prevent the theft of Inuit trading goods by English fishers. Whatever the original motivation for the killings of Nicholas Darby’s men may have been, the 1767 melee remains an important historical event in Labrador, which occurred during a decade that saw British legal and administrative changes reshape European relations with Inuit and a lasting Moravian presence on Labrador’s north coast established.